Exploration on high performance polyamide 1010/polyurethane blends filled with functional graphene nanoplatelet: physical properties and technical application. Issue 2 (3rd April 2017) - Kausar, Ayesha
ABSTRACT: In this attempt, novel polyurethane (PU) was prepared and blended with polyamide 1010 (PA1010). Based on morphology, molecular weight, polydispersity index, thermal, and shear stress behavior, PA1010/PU (80:20) blend was opted as matrix material for graphene nanoplatelet (GNP) reinforcement. PA1010/PU/GNP nanocomposites were prepared using various GNP loadings (1–5 wt.%). According to scanning electron microscopy (SEM), PA1010/PU blend with 5 wt.% PU revealed better compatibility. Inclusion of functional GNP resulted in formation of speckled morphology due to physical interaction between nanofiller and the matrix. In the case of PA1010/PU/GNP 3 nanocomposite, T0 (532 ºC) was much higher than the unfilled blend (389 ºC). Similarly, other thermal properties (T10 565 ºC; Tmax 599 ºC) of PA1010/PU/GNP 3 nanocomposite were significantly higher than the blends and nanocomposites. Limiting oxygen index measurement indicated better non-flammability of PA1010/PU/GNP 1–3 nanocomposite series (50%–57%) relative to the PA1010/PU 1–3 blend series (39%–45%). The results were supported by UL94 tests, where PA1010/PU/GNP 1–3 nanocomposites attained V-0 rating. Furthermore, PA1010/PU/GNP 3 nanocomposite showed optimum tensile strength (48 MPa), impact strength (3.9 MPa), flexural modulus (1393 MPa). Consequently, PA1010/PU/GNP 3 material was successfully used to design automotive part. Abstract :